Plasma and synovial concentrations of carprofen in dogs with chronic osteoarthritis - Schneider, T. A.; Budsberg, S. C. (Veterinary and Comparative Orthopaedics and Traumatology, 2001)
The objective of this study was to measure the synovial and plasma concentration of carprofen in normal and osteoarthritic stifle joints throughout a 12-hour period. Eight healthy male mixed breed hound dogs with chronic right stifle osteoarthritis (OA) secondary to right cruciate ligament transection, were used. Each dog was treated with carprofen (2mg/kg every 12 hours) for 14 days at four different time periods. Prior to treatment, each dog had baseline data collected that included two force plate evaluations (seven days apart), synovial fluid, and plasma collections. Plasma samples were collected at three hours post drug administration on days two, four, six, eight, 10, and 12. On days #7 and 14 plasma, serum, bilateral stifle synovial fluid and ground reaction forces (GRFs) were collected at three, six, nine, or 12 hours post-medication, depending upon the test protocol. Vertical and cranio-caudal ground reaction forces were recorded at each time period. Plasma concentrations measured at three hours remained constant over each testing protocol. There were not any differences between the plasma carprofen concentrations at three, nine, or 12 hours between days #7 or 14. A significant difference was not found in the carprofen synovial concentrations between left and right stifles at any time. Significant increases in vertical impulse data were found at six hours post-treatment, for all of the collection periods on days three, seven and 14. During the study, there was not any indication that carprofen had a ‘preference’ for the OA stifle as opposed to the normal stifle. Carprofen administration increased the total force transmitted through the abnormal limb.Carprofen concentrations in the plasma and synovial fluid and ground reaction forces were measured in dogs with single stifle osteoarthritis at three, six, nine and 12 hours following dosing at 2 mg/kg every 12 hours. Carprofen did not have a ‘preference’ for the OA stifle as opposed to the normal stifle. Carprofen administration increased the total force transmitted through the abnormal limb.
Keywords: Plasma; synovial fluid; carprofen; osteoarthritis